Editorial: Responsible well-being — a personal agenda for development - Chambers, Robert (World Development, 1997)
If development means good change, questions arise about what is good, and what sorts of change matter. Answers can be personally defined and redefined. The changing words, meanings and concepts of development d iscourse both reflect and influence what is done. The realities of the powerful tend to dominate. Drawing on experience with participatory a pproaches and methods which enable poor and marginalized people to exp ress their realities, responsible well-being is proposed as a central concept for a development agenda. This links with capabilities and liv elihoods, and is based on equity and sustainability as principles. The primacy of personal actions and non-actions in development points to the need for a pedagogy for the non-oppressed. This includes self-crit ical awareness, thinking through the effects of actions, and enabling those with power and wealth to experience being better off with less. Others are invited and encouraged to reflect, improve on this analysis , and write their own agenda.
Keywords: development vocabulary; ethics; methods; participation; poverty; well-being